Survival after an acute coronary syndrome: 18‐month outcomes from the Australian and New Zealand SNAPSHOT ACS study. Issue 9 (2nd November 2015) - Brieger, David B; Chew, Derek PB; Redfern, Julie; Ellis, Chris; Briffa, Tom G; Howell, Tegwen E; Aliprandi‐Costa, Bernadette; Astley, Carolyn M; Gamble, Greg; Carr, Bridie; Hammett, Christopher JK; Board, Neville; et al.
Abstract: Objectives: To assess the impact of the availability of a catheterisation laboratory and evidence‐based care on the 18‐month mortality rate in patients with suspected acute coronary syndromes (ACS). Design, setting and participants: Management and outcomes are described for patients enrolled in the 2012 Australian and New Zealand SNAPSHOT ACS audit. Patients were stratified according to their presentation to hospitals with or without cardiac catheterisation facilities. Data linkage ascertained patient vital status 18 months after admission. Descriptive and Cox proportional hazards analyses determined predictors of outcomes, and were used to estimate the numbers of deaths that could be averted by improved application of evidence‐based care. Main outcome measures: Mortality for ACS patients from admission to 18 months after admission. Results: Definite ACS patients presenting to catheterisation‐capable (CC) hospitals ( n = 1326) were more likely to undergo coronary angiography than those presenting to non‐CC hospitals ( n = 1031) (61.5% v 50.8%; P = 0.0001), receive timely reperfusion (for ST elevation myocardial infarction (STEMI) patients: 45.2% v 19.2%; P < 0.001), and be referred for cardiac rehabilitation (57% v 53%; P = 0.05). All‐cause mortality over 18 months was highest for STEMI (16.2%) and non‐STEMI (16.3%) patients, and lowest for those presenting with unstable angina (6.8%) and non‐cardiac chest pain (4.8%; P < 0.0001 for trend). After adjustment for patient propensity to present to a CC hospital and patient risk, presentation to a CC hospital was associated with 21% (95% CI, 2%–37%) lower mortality than presentation to a non‐CC hospital. This mortality difference was attenuated after adjusting for delivery of evidence‐based care. Conclusion: In Australia and New Zealand, the availability of a catheterisation laboratory appears to have a significant impact on long‐term mortality in ACS patients, which is still substantial. This mortality may be reduced by improvements in evidence‐based care in both CC and non‐CC hospitals.